Axion-Assisted Electroweak Baryogenesis - Craig, N; March-Russell, J (2010)
We consider a hidden-valley gauge sector, G, with strong coupling scale Lambda~TeV and CP-violating topological parameter, theta, as well as a new axion degree of freedom which adjusts theta to near zero in the current universe. If the G-sector couples to the Standard Model via weak-scale states charged under both, then in the early universe it is possible for the CP-violation due to theta (which has not yet been adjusted to zero by the hidden axion) to feed in to the SM and drive efficient baryogenesis during the electroweak (EW) phase transition, independent of the effectively small amount of CP violation present in the SM itself. While current constraints on both the new axion and charged states are easily satisfied, we argue that the LHC can investigate the vast majority of parameter space where EW-baryogenesis is efficiently assisted, while the hidden axion should comprise a significant fraction of the dark matter density. In the supersymmetric version, the ``messenger'' matter communicating between the SM- and G-sectors naturally solves the little hierarchy problem of the MSSM. The connection of the hidden scale and masses of the ``quirk''-like messengers to the EW scale via the assisted electroweak baryogenesis mechanism provides a reason for such new hidden valley physics to lie at the weak scale.